Epidemiological Overview of Type 2 Diabetes Mellitus at Konawe Kepulauan Hospital in 2024 - Cici Wulandari Asmun; Maryus Manga; Nurliana; Rini Agustia Amin (Journal of Health Science and Pharmacy, 2026)
Background: A chronic, non-communicable condition called diabetes mellitus is typified by high blood glucose levels brought on by a malfunctioning insulin system. This condition has grown to be a public health concern, with prevalence continuing to rise annually. Objectives: Determining the epidemiological spread of Type 2 Diabetes Mellitus was the goal of this investigation based on gender, age group, and wound complications at Konawe Kepulauan Hospital in 2024. Methods: A quantitative descriptive approach was applied using secondary data from inpatient and outpatient medical records collected in 2024. Results: A total of 169 patients were recorded, comprising 52.0% males and 46.7% females. The most affected age group was 40–59 years (63.3%), followed by 60–79 years (34.3%). Wound complications occurred in 15.4% of patients, with a higher proportion among inpatients (18.8%). Conclusion: Type 2 Diabetes Mellitus is most prevalent among middle-aged and elderly individuals, with wound complications more commonly observed in hospitalized patients. Keywords: Type 2 Diabetes Mellitus, gender, age, wound complications.